2018
DOI: 10.1155/2018/6470137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tofogliflozin on Body Composition and Glycemic Control in Japanese Subjects with Type 2 Diabetes Mellitus

Abstract: Sodium-glucose cotransporter 2 inhibitor tofogliflozin is a new type of antidiabetic drug for individuals with type 2 diabetes mellitus (T2DM). The aim of this study was to examine in which type of individuals and/or under which conditions tofogliflozin could exert more beneficial effects on body composition and/or glycemic control in Japanese individuals with T2DM. We retrospectively evaluated the effects of tofogliflozin on body composition and/or glycemic control in individuals with T2DM who newly started t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
3
29
2
Order By: Relevance
“…In this study, we showed that canagliflozin as add-on therapy to teneligliptin exerted beneficial effects on metabolic parameters such as body weight, HbA1c, and uric acid without any severe adverse events (Table 1), which were compatible with the previous reports about the effectiveness of SGLT2 inhibitors [10][11][12]. In addition, in the univariate analysis, HbA1c levels at baseline were strongly associated with ΔHbA1c (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we showed that canagliflozin as add-on therapy to teneligliptin exerted beneficial effects on metabolic parameters such as body weight, HbA1c, and uric acid without any severe adverse events (Table 1), which were compatible with the previous reports about the effectiveness of SGLT2 inhibitors [10][11][12]. In addition, in the univariate analysis, HbA1c levels at baseline were strongly associated with ΔHbA1c (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…17,18 Overall, the degree of weight loss with SGLT2i(s) is modest at approximately 3 kilograms; there is a net loss of body water and electrolytes during the first 4 weeks of treatment that is followed by a preferential loss of fat mass. 20,22 Based on the positive effects of SGLT2i(s) on reducing body weight, total body and visceral fat mass, and reducing serum AST and ALT levels, studies were initiated to test the efficacy of these agents on NAFLD. 15,16,28,49,51,52 The effect of SGLT2i(s) on the metabolic abnormalities present in patients with NAFLD ( Figure 2) is depicted in Figure 3.…”
Section: Sglt-2 Co-transporter Its Inhibitors and Their Role In Hepmentioning
confidence: 99%
“…Benefits include weight loss with decreases in total and visceral fat, hepatic fat content, transaminase levels, blood glucose and insulin levels and insulin resistance; additional benefits include improvements in metabolic and inflammatory parameters, and possibly lower rates of liver fibrosis and HCC. 15,16,[20][21][22][23] To prepare this analysis, PubMed was searched for the published literature in English from 1990 to 2019 for the pathogenesis, diagnosis, and treatment of NAFLD, and for SGLT2i(s) and their use in patients with NAFLD. Based on this search, relevant references were selected for this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…One study suggested that tofogliflozin functions as a preventive agent for liver tumorigenesis via attenuation of chronic inflammation and hepatic steatosis (Obara et al, ). It is recommended for T2DM patients who are relatively obese with a short duration of diabetes (about 1 year; Kamei et al, ).…”
Section: Phlorizinmentioning
confidence: 99%